2021
DOI: 10.31989/ffhd.v11i11.818
|View full text |Cite
|
Sign up to set email alerts
|

Functional foods’ bioactive components and their chemoprevention mechanism in cervical, breast, and liver cancers: A systematic review

Abstract: The invasiveness and low survivability on the part of patients associated with cancer continues to raise global concern. Different approaches have been used in the treatment and restoration of normalcy in cancer patients. However, most of the therapeutic strategies employed are challenged with high cost, low efficacy, high toxicity, and multiple side effects. In recent times, emergent studies have provided evidence that functional foods and their bioactive components serve roles as potential agents in the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Furthermore, a recent study showed that IVN attenuates kindling in rats through its antioxidant effects (Ahmed et al 2020 ). Of note, exaggeration of inflammatory reactions and oxidative stress may induce the development of heart failure (Onohuean et al 2021 ; Teibo et al 2021 ). These findings suggest that the anti-inflammatory and antioxidant properties of IVN could be a potential mechanism in reducing DXR-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study showed that IVN attenuates kindling in rats through its antioxidant effects (Ahmed et al 2020 ). Of note, exaggeration of inflammatory reactions and oxidative stress may induce the development of heart failure (Onohuean et al 2021 ; Teibo et al 2021 ). These findings suggest that the anti-inflammatory and antioxidant properties of IVN could be a potential mechanism in reducing DXR-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-based medicines has shown potent anti-cancer, anti-diabetic, anti-viral and neuroprotective effect [75][76][77]. Notable pros of paclitaxel's have been its usage in many cancers, high success rate from preclinical and clinical trial data, its combinatorial properties with other drugs.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…HIF is a transcription factor released in response to hypoxia and promotes survival in hypoxic conditions by the upregulation of various genes for enzyme-like glycolysis enzymes; this produce ATP independent of oxygen status, and VEGF, which promotes angiogenesis [ 134 , 135 ]. HIF is inactivated by HIF prolyl-hydroxylase, so HIF prolyl-hydroxylase inhibitors like desidustat and vadadustat inhibit renal HIF-α2; this increases the release of erythropoietin and is used for the treatment of anemia.…”
Section: Role Of Neuropilin-1 In Covid-19mentioning
confidence: 99%